2010
DOI: 10.1021/jm901893x
|View full text |Cite
|
Sign up to set email alerts
|

(1S)-1,5-Anhydro-1-[5-(4-ethoxybenzyl)-2-methoxy-4-methylphenyl]-1-thio-d-glucitol (TS-071) is a Potent, Selective Sodium-Dependent Glucose Cotransporter 2 (SGLT2) Inhibitor for Type 2 Diabetes Treatment

Abstract: Derivatives of a novel scaffold, C-phenyl 1-thio-D-glucitol, were prepared and evaluated for sodium-dependent glucose cotransporter (SGLT) 2 and SGLT1 inhibition activities. Optimization of substituents on the aromatic rings afforded five compounds with potent and selective SGLT2 inhibition activities. The compounds were evaluated for in vitro human metabolic stability, human serum protein binding (SPB), and Caco-2 permeability. Of them, (1S)-1,5-anhydro-1-[5-(4-ethoxybenzyl)-2-methoxy-4-methylphenyl]-1-thio-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 44 publications
0
111
0
Order By: Relevance
“…Preclinical studies have shown that luseogliflozin is a specific and selective SGLT2 inhibitor 15 and that luseogliflozin improved glucose tolerance and reduced hyperglycemia in animal models of diabetes 16 . In a phase I study of luseogliflozin in healthy individuals 17 and a clinical pharmacology study that assessed the pharmacokinetic and pharmacodynamic profiles of luseogliflozin in patients with T2DM 18 , luseogliflozin dose dependently increased urinary glucose excretion without causing hypoglycemia.…”
Section: Including Luseogliflozin [Ts-071; (1s)-15-anhydro-1-[5-(4mentioning
confidence: 99%
“…Preclinical studies have shown that luseogliflozin is a specific and selective SGLT2 inhibitor 15 and that luseogliflozin improved glucose tolerance and reduced hyperglycemia in animal models of diabetes 16 . In a phase I study of luseogliflozin in healthy individuals 17 and a clinical pharmacology study that assessed the pharmacokinetic and pharmacodynamic profiles of luseogliflozin in patients with T2DM 18 , luseogliflozin dose dependently increased urinary glucose excretion without causing hypoglycemia.…”
Section: Including Luseogliflozin [Ts-071; (1s)-15-anhydro-1-[5-(4mentioning
confidence: 99%
“…Because SGLT2 inhibitors have an insulin-independent mechanism of action, these are expected to improve glycemic control with a low risk of major hypoglycemic events 11 . Luseogliflozin -a novel, orally bioavailable, 1-thio-D-glucitol derivative and a highly selective inhibitor of SGLT2 9,12 -lowered glucose levels by promoting urinary glucose excretion in animal models 12 . Results from the previous 12-week exploratory and dose-finding (phases 2a and 2b, respectively) clinical studies have shown that once daily administration of luseogliflozin leads to significant improvements in HbA1c as well as other glycemic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Luseogliflozin is a novel selective SGLT2 inhibitor 5,6) currently marketed for the treatment of T2DM. The recommended dose is 2.5 mg (or 5 mg depending on the symptoms) once daily before or after breakfast.…”
Section: -4)mentioning
confidence: 99%